2016
DOI: 10.1002/ajcp.12064
|View full text |Cite
|
Sign up to set email alerts
|

On Becoming Scholars and Activists for Disability Rights

Abstract: In this paper, the authors discussed the nexus between the Americans with Disabilities Act and the founding of the field of Community Psychology. Contributions of the latter and future areas of research are reviewed here in three areas of importance to both fields: Community living and participation, employment, and transition from high school. Community psychology can make potential contributions to advancing research in these three areas. Implications for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The increase in the Latinx population has also resulted in an increase in the number of Latinxs with disabilities (Balcazar, Magaña, & Suarez-Balcazar, 2020). Latinxs with disabilities often lack knowledge about special education services and supports, independent living, disability-related laws like the Americans with Disabilities Act (ADA), and services like vocational rehabilitation, which supports employment opportunities after graduation from high school (Balcazar & Suarez-Balcazar, 2017). In addition, Latinx young adults with disabilities are more likely than those without disabilities and more likely than White youth with disabilities to experience health disparities and have poor health outcomes (Balcazar et al, 2020;Magaña et al, 2015).…”
Section: Theoretical Background In Contextmentioning
confidence: 99%
“…The increase in the Latinx population has also resulted in an increase in the number of Latinxs with disabilities (Balcazar, Magaña, & Suarez-Balcazar, 2020). Latinxs with disabilities often lack knowledge about special education services and supports, independent living, disability-related laws like the Americans with Disabilities Act (ADA), and services like vocational rehabilitation, which supports employment opportunities after graduation from high school (Balcazar & Suarez-Balcazar, 2017). In addition, Latinx young adults with disabilities are more likely than those without disabilities and more likely than White youth with disabilities to experience health disparities and have poor health outcomes (Balcazar et al, 2020;Magaña et al, 2015).…”
Section: Theoretical Background In Contextmentioning
confidence: 99%
“…These factors are significant barriers that are deconstructed and eliminated to enhance social justice for individuals with disabilities. For instance, Balcazar and Suarez‐Balcazar (2016) and Suarez‐Balcazar et al (2022) identified employment, education, and environmental barriers in the infrastructure associated with issues of economic justice and citizen participation. Soffer et al (2010) addressed the barriers in policies and societal values regarding asset accumulation and income for people with disabilities, leading to extreme economic injustice.…”
Section: Methodsmentioning
confidence: 99%
“…We identified three papers that focused collectively on case studies illustrative of disability social justice projects and interventions that aim to enact other key principles of community psychology. Balcazar and Suarez‐Balcazar (2016) discussed the interaction between disability research and the field of community psychology by showcasing interventions in three areas: community living and participation, employment, and transition from high school. Similarly, in Suarez‐Balcazar et al (2022), three international case studies are presented that illustrate different interventions aimed at promoting social justice among groups experiencing marginalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a background in community activism from their native Bogota, Columbia, Balcazar and Suarez‐Balcazar () describe their training in community psychology in the 1980s as each obtained their doctoral degree in developmental and child psychology. They also describe their introduction to research and practice on individuals with disabilities, which eventually became their life's work.…”
Section: Introduction To the Special Issue: Reflections On Community mentioning
confidence: 99%